Letter : Shoes for Spanish refugees - Stolz, George
032-0037-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, Avenue d'Orsay, Paris-VIIe ST/T TELEGRAMS: INTERFED—PARIS TELEPHONE: INVALIDES 45-88 AFFILIATED COUNTRIES: ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA EXECUTIVE COMMITTEE: President W. M. Citrine, Great Britain; Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E. Kupers, Holland; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia; General Secretary: W. Schevenels. Letter: F. I. de Sol No. 813 16th June, 1939. Mr. E.A. Bell, Trades Union Congress, Transport House, Smith Square, London, S.W.1. Dear Mr. Bell, Shoes for Spanish Refugees. With reference to our telephone conversation of the 9th June, can you let us know how many pairs of shoes there are in each of the packages? We are anxious to have this information as the C.W.S. in Rouen inform us that if they cannot distribute the packages, storage costs will arise. Can you, therefore, let us have the necessary information as soon as possible? Yours sincerely, G. Stolz, Assistant Secretary. 292/946/32/37